NOD2 Polymorphisms and Pulmonary Tuberculosis Susceptibility: A Systematic Review and Meta-Analysis - Wang, Chong (Ivyspring International Publisher, 2013)
The association between NOD2 and tuberculosis (TB) risk has been reported widely, but the results of previous studies remained controversial and ambiguous. To assess the association between NOD2 polymorphisms and TB risk, a meta-analysis was performed. A literature search was conducted by using the PubMed, Ovid, ISI Web of Knowledge, Elsevier ScienceDirect, and Chinese National Knowledge Infrastructure (CNKI). We identified the data from all articles estimating the association between NOD2 polymorphisms and TB risk. In total, 2,215 cases and 1,491 controls in 7 case-control studies were included. In meta-analysis, we found significant association between the Arg702Trp polymorphism and TB risk (OR = 0.43, 95% CI = 0.20-0.90, P = 0.02). However, no significant association was found between the Arg587Arg (OR = 1.31, 95% CI = 0.83-2.07, P = 0.25) and Gly908Arg (OR = 0.78, 95% CI = 0.21-2.87, P = 0.71) polymorphisms and TB risk. The present meta-analysis suggested that NOD2 Arg702Trp polymorphism was likely to be a protective factor for TB. However, the Arg587Arg and Gly908Arg polymorphisms might not be the genetic risk factors for TB susceptibility.